Steering e-Government Projects from Failure to Success : Using Design-Reality Gap Analysis as a Mid-Implementation Assessment Tool /: Using Design-Reality Gap Analysis as a Mid-Implementation Assessment Tool. (2012) - Lessa, Lemma; Negash, Solomon, 1960-; Belachew, Mesfin
No abstract available